2011
DOI: 10.5194/angeo-29-1873-2011
|View full text |Cite
|
Sign up to set email alerts
|

Observations of OI 557.7 nm nightglow at Kolhapur (17° N), India

Abstract: The nocturnal behaviour of OI 557.7 nm intensity and a comparative study with simultaneous OH Meinel band temperature measurements has been presented. OI 557.7 nm intensity and OH temperature variations covary on many occasions. It was found that an 8 h tide characterizes the variation of intensity and temperature on most nights, and especially during the month of January. This is the first report of prolonged measurements of OI 557.7 nm emission from India.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 46 publications
(65 reference statements)
2
2
0
Order By: Relevance
“…Using MLTP observations during April and July 2009, Taori et al (2012a, c) presented the observations of gravity wave activity in OH and O 2 temperatures over Gadanki, whereas Taori et al (2012b) found semiannual oscillations in two temperatures during April 2009-March 2011. The nocturnal behaviour of the intensity of OI 557.7 nm emission, noted in the present study, is quite similar to that reported earlier from the current observation site by Parihar et al (2011), and hence, a brief report of observations of OI 557.7 nm emission during FebruaryMarch 2007 has been presented here.…”
Section: Introductionsupporting
confidence: 75%
See 1 more Smart Citation
“…Using MLTP observations during April and July 2009, Taori et al (2012a, c) presented the observations of gravity wave activity in OH and O 2 temperatures over Gadanki, whereas Taori et al (2012b) found semiannual oscillations in two temperatures during April 2009-March 2011. The nocturnal behaviour of the intensity of OI 557.7 nm emission, noted in the present study, is quite similar to that reported earlier from the current observation site by Parihar et al (2011), and hence, a brief report of observations of OI 557.7 nm emission during FebruaryMarch 2007 has been presented here.…”
Section: Introductionsupporting
confidence: 75%
“…4 depicts an example of such a feature -the variation of O 2 temperature is fairly steady, whereas the one of OH is marked by oscillations having periodicity of ∼2 h. From an analysis for the short period variations in the OH temperature series, the oscillations having periodicities in the range of 1-2 h dominate the spectrum of gravity wave activity near the OH emission peak. Parihar et al (2011) had similar observations for concurrent database of OH temperature and OI 557.7 nm emission intensity (i.e. the short-period oscillations observed in OH temperature series were not seen in OI 557.7 nm intensity data) on most occasions.…”
Section: Derivation Of Oh and O Rotational Temperaturessupporting
confidence: 61%
“…The mesospheric OH and O ( 1 S) emission monitoring is done with the help of a photomultiplier tube (EMI-9658B) based photometer having a full field of view of 10 ∘ . The temperature stabilized interference filters are mounted on a computer controlled filter-wheel with integration time at each filter ∼10 s. The interference filters mounted on filter-wheel have full width and half maxima of ∼ 0.8 nm and are maintained at 25 ∘ C. Details of the instrument and method of temperature retrieval are discussed elsewhere [22]. The errors arising due to the photomultiplier electronics (dark current and readout noise) and filter movement are about 0.2% at 25 ∘ C. The present data are obtained for zenith viewing during February and March 2010 when clear, moonless night conditions allowed more than 6 hours of observations consecutively for 14 nights.…”
Section: Mesospheric Airglow Datamentioning
confidence: 99%
“…In the thermosphere around 250 km, the 630 nm emission intensity strongly depends on the density of O ion, O molecule and electrons in the F‐region. In addition, the intensity decreases when the ionospheric layer moves up and vice versa (Parihar et al., 2012).…”
Section: Resultsmentioning
confidence: 99%